1986
DOI: 10.1007/bf00181249
|View full text |Cite
|
Sign up to set email alerts
|

The effects of (+)-amphetamine and apomorphine on responding for a conditioned reinforcer

Abstract: Two psychomotor stimulants, (+)-amphetamine and apomorphine, were examined for effects on associative learning and responding for a conditioned reinforcer. The experimental phases included: preexposure to an operant test chamber with two levers, each of which produced a neutral stimulus when pressed; pairings of one stimulus with food; and a subsequent test of lever pressing for the two stimuli. Groups of food deprived rats (n = 8-12) were given IP injections of one stimulant prior to each pairing or testing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…This observation fits with the well-known ability of acute amphetamine to increase the response to conditioned cues (Robbins, 1978;Beninger et al, 1981;Robbins et al, 1983;Mazurski and Beninger, 1986). Indeed, the increase in collect responses made following amphetamine administration could simply be another example of this drug's ability to increase prepotent responding for reward, as exemplified by increased response rates on differential reinforcement of low rate schedules (Segal, 1962;Sanger, 1978) and elevated premature responding on the five-choice serial reaction time task (Cole and Robbins, 1987;Harrison et al, 1997).…”
Section: Discussionsupporting
confidence: 74%
“…This observation fits with the well-known ability of acute amphetamine to increase the response to conditioned cues (Robbins, 1978;Beninger et al, 1981;Robbins et al, 1983;Mazurski and Beninger, 1986). Indeed, the increase in collect responses made following amphetamine administration could simply be another example of this drug's ability to increase prepotent responding for reward, as exemplified by increased response rates on differential reinforcement of low rate schedules (Segal, 1962;Sanger, 1978) and elevated premature responding on the five-choice serial reaction time task (Cole and Robbins, 1987;Harrison et al, 1997).…”
Section: Discussionsupporting
confidence: 74%
“…Here we show that amphetamine enhances reinforcing efficacy regardless of the cues' initial incentive value. This broad effect on behavior may be unique to psychostimulants compared to other drugs, and may be related to its ability to enhance the reinforcing efficacy of a broad class of cues [40], [74][81]. For example, the ability of nicotine to enhance the reinforcing effect of visual stimuli was systematically related to the strength of the reinforcer [82].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies that have reported the effects of d -amphetamine on responding for CRs [22, 34, 35, 37, 3941]. In general, these studies report increases in the absolute rate of active responding and smaller, less consistent increases in the absolute rates of inactive responding.…”
Section: Discussionmentioning
confidence: 99%